The effect of plasma generated ozone for cold storage the broiler chicken meat - MERISA MERISA YULIANI; L D MAHFUDZ; NURWANTORO NURWANTORO; M NUR (Nusantara Bioscience, 2019)
Yuliani M, Mahfudz LD, Nurwantoro, Nur M. 2019. The effect of plasma generated ozone for cold storage the broiler chicken meat. Nusantara Bioscience 11: 12-17.  The aim of this study was to determine the effect of combination treatment washing chicken meat with three ozone concentrations in the water during 10 min and stored at 2-7?C without ozonation and with ozonation, on the shelf life of chicken meat. The study was conducted with a complete random factorial design (CRD) factorial pattern 3 x 2 with 3 replications. The data were analyzed by using analysis of variance (ANOVA). If the results were significant, the analysis followed Duncan's New Multiple Range Test (DMRT). The results of statistical analysis showed that average pH values, color scores intensity b * for brightness (yellowness) and Peroxide value (PV) showed significant differences (P <0.05). H 2 S test showed that combination treatment washing chicken meat with ozone concentrations 3ppm in the water during 10 min and stored at 2-7?C with ozonation was able to inhibit the start process of decomposition chicken meat until the 10th days. The conclusion of these results that combination treatment washing chicken meat with ozone concentrations 3ppm in the water during 10 min and stored at 2-7?C with ozonation can extend the shelf life of chicken meat until the 10th days.